Pembangunan set perlakuan dalam persekitaran kolaboratif berasaskan multi-user dimension object oriented (MOO) untuk pengajaran dan pembelajaran bahasa: kajian kes di KUSZA - Mat Amin, Mat Atar (2005)
MUD Object Oriented (MOO) is a text based collaborative system that supports Computer Supported Collaborative Learning (CSCL). It has a potential to be applied as a support system to the collaborative language teaching and learning. Educational MOO is an extension of MOO that is specially designed with its collaborative teaching and learning system characteristic. This research is developed to identify appropriate sets of verbs used in virtual classrooms. The purpose is to investigate the effectiveness of MOO in supporting collaborative activities and its role in creating effective collaborative teaching and learning activities. An educational MOO prototype called kusMOO has been developed based on the identified needs derived from the lecturers. This is followed by ADDIE (Analysis, Design, Development, Implementation and Evaluation) a prototype model. The model consists of five phases namely analysis, design, development, implementation and evaluation. UML was chosen to model the system design. Testing was done to find out whether the sets of verbs chosen were able to support the effectiveness of collaborative activities and to enhance the language skills of the students. The results showed that these appropriate sets of verbs can be a value added activity to the teaching and learning of collaborative MOO. It has been proven that its effectiveness and role were able to fulfill the needs of collaborative teaching and learning language environment. The use of the sets of verbs has opened up the potential of MOO as a new innovation for the needs of collaborative teaching and learning and at the same time contribute as a new finding to the CSCL.